Experimental analysis of the thermal entrainment factor of air curtains in vertical open display cabinets for different ambient air conditions - Gaspar, Pedro Dinis (2019)
The vertical open refrigerated display cabinets suffer alterations of their thermal performance and energy efficiency due to variations of ambient air conditions. The air curtain provides an aerothermodynamics insulation effect that can be evaluated by the thermal entrainment factor calculation as an engineering approximation or by the calculus of all sensible and latent thermal loads. This study presents the variation of heat transfer rate and thermal entrainment factor obtained through experimental tests carried out for different ambient air conditions, varying air temperature, relative humidity, velocity and its direction relatively to the display cabinet frontal opening. The thermal entrainment factor are analysed and compared with the total sensible and latent heats results for the experimental tests. From an engineering point of view, it is concluded that thermal entrainment factor cannot be used indiscriminately, although its use is suitable to design better cabinet under the same climate class condition.